CONTINENTAL BREAK-UP AND COLLISION IN THE NEOPROTEROZOIC AND PALAEOZOIC - A TALE OF BALTICA AND LAURENTIA - Torsvik T.H.; Smethurst M.A.; Sturt B.A.; Meert J.G.; Van der Voo R.; Walderhaug H.J.; McKerrow W.S.; Brasier M.D. (My University, 1996)
During the Neoproterozoic and Palaeozoic the two continents of Baltica and Laurentia witnessed the break-up of one supercontinent, Rodinia, and the formation of another, but less long-lived, Pangea. Baltica and Laurentia played central roles in a tectonic menage a trois that included major orogenic events, a redistribution of palaeogeography and a brief involvement of both with Gondwana. Many of these plate re-organisations took place over a short time interval and invite a re-evaluation of earlier geodynamic models which limited the speeds at which large continental plates could move to an arbitrarily low value.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская